Go live! turn virtual connections into paying customers - Gitomer, Jeffrey (Gildan Audio, 2020)
Learn how to go online with a winning sales and marketing strategyGo Live!: Turn Virtual Connections into Paying Customers helps listeners understand and take advantage of several online tools to boost their sales and increase their revenue. Accomplished salesperson, consultant, and online personality Jeffrey Gitomer describes how tools like Facebook Live and podcasting can drive sales and help you connect with your customers. You'll discover:- How to use tools like YouTube, LinkedIn Live, podcasting, and Facebook Live to connect with and develop your leads- How to properly utilize social media like Instagram and Twitter to spread your message and sell to clients- How to promote and repurpose content to create as big an impact on your audience as possibleWritten specifically for a post-pandemic sales audience, Go Live!: Turn Virtual Connections into Paying Customers delivers results for anyone expected to deliver sales results in a virtual environment. It also belongs on the bookshelves of those who hope to take their successful offline sales strategies to the online world.